Investigation of CRISPR-Independent Phage Resistance Mechanisms Reveals a Role for FtsH in Phage Adsorption to Streptococcus thermophilus - Garrett, Sandra C.; Philippe, Cecile; Kim, Jenny G.; Wei, Yunzhou; Johnson, Katie A.; Olson, Sara; Graveley, Brenton R.; Terns, Michael P. (Journal of bacteriology, 2023)
Streptococcus thermophilus is an important organism for production of cultured dairy foods, but it is susceptible to lytic phages which can lead to failed products. Consequently, mechanisms for phage resistance are an active area of research. Prokaryotes are under constant pressure from phage infection and thus have evolved multiple means of defense or evasion. While CRISPR-Cas constitutes a robust immune system and appears to be the predominant means of survival for Streptococcus thermophilus when facing lytic phage infection, other forms of phage resistance coexist in this species. Here, we show that S. thermophilus strains with deleted CRISPR-Cas loci can still give rise to phage-resistant clones following lytic phage challenge. Notably, non-CRISPR phage-resistant survivors had multiple mutations which would truncate or recode a membrane-anchored host protease, FtsH. Phage adsorption was dramatically reduced in FtsH mutants, implicating this protein in phage attachment. Phages were isolated which could bypass FtsH-based resistance through mutations predicted to alter tape measure protein translation. Together, these results identify key components in phage propagation that are subject to mutation in the molecular arms race between phage and host cell. IMPORTANCE Streptococcus thermophilus is an important organism for production of cultured dairy foods, but it is susceptible to lytic phages which can lead to failed products. Consequently, mechanisms for phage resistance are an active area of research. One such mechanism is CRISPR-Cas, and S. thermophilus is a model organism for the study of this form of adaptive immunity. Here, we expand on known mechanisms with our finding that spontaneous mutations in ftsH , a gene encoding a membrane-anchored protease, protected against phage infection by disrupting phage adsorption. In turn, mutations in phage tail protein genes allowed phages to overcome ftsH -based resistance. Our results identified components in phage propagation that are subject to mutation in the molecular arms race between phage and host.